Akustik Ruang Perkuliahan Di Unnes: Analisis Reverberation Time, Noise Distribution, Speech Intelligibility - Negoro, Ridho Adi (Pendidikan Fisika, FKIP, Universitas Nahdlatul Ulama Cirebon, 2023)
Evaluation of reverberation time, noise distribution, and speech intelligence is an important part of educational spatial planning, especially related to the comfort and feasibility of student learning. Reverberation Time, Noise Distribution, and Speech Intelligence are objective parameters commonly used to assess the acoustic quality of a room, according to its intended use. This study aims to measure the parameters of Reverberation Time, Noise Distribution, and Speech Intelligibility using the impulse response method where the results are used as evaluation material for designing or improving the spatial layout of lectures in the PPS UNNES building. The results showed that several room constructions needed to be changed because there was a lot of outside noise coming in, the Reverberation time did not meet the ANSI-60 standard. Based on the results of the study it can be concluded that the lecture rooms in the PPS UNNES building meet the eligibility which refers to ANSI-60 with certain considerations